(untitled) (Journal of Medical & Health Sciences Review, 2025)
This research paper explored the changing presence of clinical engineering in the telemedicine environment in Pakistan and the challenges and opportunities of the healthcare sector. To address research hypotheses, a mixed-methodology study was used that included both quantitative surveys conducted among 150 clinical engineers, biomedical technicians, and healthcare administrators in major Pakistani cities and qualitative interviews involving 25 key stakeholders. The study found that there are great infrastructure problems, such as poor technological facilities, poor internet networks and inadequate training of clinical engineering personnel. But there were significant opportunities arising, especially in remote patient monitoring, standardization of equipment maintenance, and improvement of healthcare access. The findings revealed that 78 percent of the surveyed respondents cited equipment reliability as the most significant challenge, whereas 85 percent of respondents acknowledged the potential of telemedicine to deliver healthcare services to underserved communities. It was discovered that clinical engineers contributed significantly towards system integration, quality assurance, and technical assistance, but their efforts were not appreciated in organizational hierarchies. Policy gaps and regulations were other obstacles to successful implementation of telemedicine. The results hint towards the possibility that enhancing clinical engineering skills by means of specific training and investing in infrastructure and better policy frameworks may be a key in promoting the Pakistan telemedicine efforts, which may eventually lead to better healthcare delivery to both urban and rural populations.